Implementation of the Numeracy Literacy Program in Learning Mathematics Remaining Class IV in Muhammadiyah Elementary Schools - Beti Istanti Suwandayani; Yahya Fakhruddin; Leny Suryaning Astutik (Universitas Muhammadiyah Surabaya, 2020)
Government programs in fostering a culture of reading and making students literate individuals are welcomed by the implementers of the education program. The purpose of this study was to analyse the implementation of the numeracy literacy in mathematics learning, to analyse the supporting and inhibiting factors of numeracy literacy program in grade IV mathematics learning in elementary schools. This research use descriptive qualitative approach. Data collection uses observation, in-depth interviews, and documentation studies. This study also uses research instruments to guide data collection. This research was conducted in several Muhammadiyah elementary schools, they are SD Muhammadiyah 1 and SD Muhammadiyah 5 Kota Malang. The subjects in this study were the principal as policy makers, class IV teachers, students and parents. The results showed that in learning numeracy literacy was good enough in contextual and problem-based concept planting, but rarely used projection based learning. Facilities and infrastructures that need to be improved, learning motivation is also an inhibiting factor in learning, but there are supporting factors such as the allocation of funds themselves for numeracy literacy programs and the existence of teacher training for literacy programs able to correct existing problems.